2018
DOI: 10.1007/s40333-018-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water deficiency on relationships between metabolism, physiology, biomass, and yield of upland cotton (Gossypium hirsutum L.)

Abstract: Drought is a common abiotic stress that considerably limits crop production. The objective of this study is to explore the influence of water deficiency on the yield, physiologic and metabolomic attributes in upland cotton cultivars (Gossypium hirsutum L). Cotton cultivars, 'Ishonch' and 'Tashkent-6' were selected to study the relationships among their physiologic, metabolomic and yield attributes during water deficiency. Deficit irrigation was designed by modifying the traditional watering protocol to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
5
14
0
Order By: Relevance
“…This can be explained by the amount of water used, which was 675 L water m −2 for full irrigation and 472 L m −2 for deficit irrigation in the field, and 566 (control) and 283 L m −2 (stress) in the managed treatment plots. It has been shown that cotton demonstrates yield reduction under water deficiency created either by drip or surface irrigation (Basal et al, 2009;Yang et al, 2015a;Bozorov et al, 2018). Moreover, yield changes in managed treatment plots were consistent with a recent study in which similar deficit surface irrigation was used with different cotton genotypes (Bozorov et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This can be explained by the amount of water used, which was 675 L water m −2 for full irrigation and 472 L m −2 for deficit irrigation in the field, and 566 (control) and 283 L m −2 (stress) in the managed treatment plots. It has been shown that cotton demonstrates yield reduction under water deficiency created either by drip or surface irrigation (Basal et al, 2009;Yang et al, 2015a;Bozorov et al, 2018). Moreover, yield changes in managed treatment plots were consistent with a recent study in which similar deficit surface irrigation was used with different cotton genotypes (Bozorov et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that cotton demonstrates yield reduction under water deficiency created either by drip or surface irrigation (Basal et al, 2009;Yang et al, 2015a;Bozorov et al, 2018). Moreover, yield changes in managed treatment plots were consistent with a recent study in which similar deficit surface irrigation was used with different cotton genotypes (Bozorov et al, 2018). The improved tolerance and yield of transgenic cotton plants are perhaps a result of improved photosynthetic homeostasis, manifested as an increased number of fruiting branches and bolls ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To identify heat tolerance, it is therefore important to ensure that variations in absorbance values from the HSA represent heat tolerance and resistance, and not water de ciencies, so plants should be kept well-watered. Finally, as responses to water stress vary among genotypes (39) and this study was only conducted in one genotype, further studies investigating the probable presence of genotype rank changes when samples are collected under water stress conditions should be conducted.…”
Section: Discussionmentioning
confidence: 99%